Gossypiboma! Never again: A case report - Bastakoti, Shankar; Lamichhane, Nirmal; Shrestha, Binuma (Nepal Mediciti Medical Journal, 2020)
Gossypiboma refers to a retained sponge in the surgical bed. We present a 40- year-old female from Terai region of Nepal presented with long standing abdominal discomfort which on further radiological examination complex adnexal mass was suspected. She had a history of emergency laparotomy for post-partum hemorrhage more than a decade ago. She underwent surgery for suspicious complex adnexal mass. On exploring fiber formed partly degenerated content was revealed, which on histopathology reveal foamy macrophages, degenerated material and fiber strands and finally diagnosis of Gossypioma was made. Prevention of gossypiboma is much better than cure.